The environmental effects on the quality parameters and chemical composition of ostrich eggs - Brassó, Lili Dóra; Komlósi, István; Szabó, Csaba; Várszegi, Zsófia (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
The study aimed to investigate the effects of laying month and environmental temperature (May: 20 ºC; July: 27 ºC) on ostrich egg quality and chemical composition. The diet components were the same in the examined period. In May, five eggs, in July, six eggs were involved in the study from the same farm. The outer egg quality parameters included egg weight (g), length (cm), width (cm), shape index (%), egg volume (g/cm3), specific gravity (g/cm3), shell colour (L*, a*, b*), shell thickness (mm), shell surface (cm2) and shell density (g/cm3). The inner quality characteristics were shell weight (g) and ratio (%), albumen weight (g) and ratio (%), yolk weight (g) and ratio (%), yolk diameter (cm), yolk colour (L*, a*, b*) and the pH of albumen and yolk. Egg composition was measured from a mixed and homogenised sample of albumen and yolk. The chemical composition comprehended dry matter (%), crude protein (%) and crude fat content (%), mineral composition (Ca, Mg, P, Zn, Cu, Fe, K, Na, S, Mn; mg/kg), the ratio of saturated (%), mono-unsaturated (%) and poly-unsaturated fatty acids (%) and saturated/unsaturated fatty acid ratio of egg and the mineral composition of eggshell. The results showed that shell thickness, yolk diameter and yolk pH were lower in July at 27 ºC than in May at 20 ºC. The crude protein and amino acid content of eggs were also lower in July compared to May. The egg saturated fatty acid content and saturated/unsaturated fatty acid ratio increased, while the content of mono-unsaturated and poly-unsaturated fatty acid content decreased in July. The mineral composition of the egg declined or remained unchanged, however the Mg content increased. The content of Ca, K, Mg and S of the eggshell increased in the examined period. The effect of the examined factors was the most obvious in the case of egg chemical composition but significant differences could be observed in egg quality parameters, as well.